2015
DOI: 10.18632/oncotarget.6138
|View full text |Cite
|
Sign up to set email alerts
|

SMAC mimetic Debio 1143 synergizes with taxanes, topoisomerase inhibitors and bromodomain inhibitors to impede growth of lung adenocarcinoma cells

Abstract: Targeting anti-apoptotic proteins can sensitize tumor cells to conventional chemotherapies or other targeted agents. Antagonizing the Inhibitor of Apoptosis Proteins (IAPs) with mimetics of the pro-apoptotic protein SMAC is one such approach. We used sensitization compound screening to uncover possible agents with the potential to further sensitize lung adenocarcinoma cells to the SMAC mimetic Debio 1143. Several compounds in combination with Debio 1143, including taxanes, topoisomerase inhibitors, and bromodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
2
18
0
4
Order By: Relevance
“…BRD induced oncogenic signaling appears to be pervasive in all breast cancer subtypes (25); disrupting BRD function in basal-like breast cancer suppressed tumorigenesis (26), and TNBCs appear to be preferentially sensitive to BRD inhibition (27). We have recently reported anticancer activity of JQ1 in drug combinations in vitro and in vivo (28). Interestingly, JQ1 was also found to synergize with RTK inhibitors, erlotinib, XL-184, and crizotinib.…”
Section: Resultsmentioning
confidence: 99%
“…BRD induced oncogenic signaling appears to be pervasive in all breast cancer subtypes (25); disrupting BRD function in basal-like breast cancer suppressed tumorigenesis (26), and TNBCs appear to be preferentially sensitive to BRD inhibition (27). We have recently reported anticancer activity of JQ1 in drug combinations in vitro and in vivo (28). Interestingly, JQ1 was also found to synergize with RTK inhibitors, erlotinib, XL-184, and crizotinib.…”
Section: Resultsmentioning
confidence: 99%
“…Several of our top combinations affected immune/inflammatory signaling pathways. Immune signaling is an important component of PDAC development (34-36) and apoptosis modulators work in conjunction with immune response signaling pathways, such as JAK/STAT3/NF-κB axis control of BCL-2 expression (37). STAT3 promotes PDAC with mutant KRAS in PDAC mouse models (38).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that targeting of IAPs or BCL-2 family members could be beneficial for paclitaxel-treated TNBC patients. Indeed, it was shown that SMAC mimetics potentiate paclitaxel-mediated ovarian cancer cell death in vitro and in vivo [35] and similar effects were reported for NSCLC [14, 15] and breast cancer [16]. Likewise, administration of navitoclax (ABT-263) enhanced taxane-based treatment of ovarian cancer [36] and NSCLC [37].…”
Section: Discussionmentioning
confidence: 87%